Highly Efficient Proton Conduction in a Three-Dimensional Titanium Hydrogen Phosphate - Mileo, Paulo G. M; Kundu, Tanay; Semino, Rocio; Benoit, Virginie; Steunou, Nathalie; Llewellyn, Philip L; Serre, Christian; Maurin, Guillaume; Devautour-Vinot, Sabine (Chemistry of materials, 2017)
Force field-based and ab initio molecular dynamics simulations are combined with impedance spectroscopy experiments to reveal the high proton conduction performance of a three-dimensional titanium phosphate TiIVTiIV(HPO4)4 under humidity and further elucidate the microscopic mechanism at the origin of the proton transport throughout the porosity of this solid. The molecular simulations revealed that the POH groups in the structure act as a proton source, and the proton is transported from one pore to another through the hydrogen bond network formed by water molecules and the bridging O of the solid. Propitiously, besides its superprotonic behavior with a conductivity of 1.2 × 10–3 S cm–1 at room temperature and 95% relative humidity, this material is one of the best porous solids reported to date in terms of efficiency for proton transfer with a resulting activation energy (0.13 eV) as low as that reported for Nafion commercially used as electrolyte membrane in fuel cells. Furthermore, this solid shows a spectacular increase of the conductivity by 9 orders of magnitude at 90 °C when the relative humidity goes from 0 to 95%. This makes TiIVTiIV(HPO4)4 as a potential candidate for humidity sensor applications.